Characterization of Differentially Detectable Mycobacterium tuberculosis in the Sputum of Subjects with Drug-Sensitive or Drug-Resistant Tuberculosis before and after Two Months of Therapy - Zainabadi, Kayvan; Walsh, Kathleen Frances; Vilbrun, Stalz Charles; Mathurin, Laurent Daniel; Lee, Myung Hee; Saito, Kohta; Mishra, Saurabh; Ocheretina, Oksana; Pape, Jean William; Nathan, Carl; Fitzgerald, Daniel W. (Antimicrobial agents and chemotherapy, 2021)
Standard methods for enumerating Mycobacterium tuberculosis in patient sputum can miss large populations of viable M. tuberculosis cells that are unable to grow either on solid medium or in liquid medium unless the medium has been extensively diluted. Because these bacteria can be detected in liquid medium after limiting dilution, they have been termed differentially culturable or differentially detectable M. tuberculosis (DD- Mtb ). Treatment with isoniazid (H), rifampin (R), pyrazinamide (Z), and ethambutol (E) (HRZE) for 1 to 2 weeks has been shown to increase the representation of DD- Mtb in the sputum of drug-sensitive (DS) tuberculosis (TB) patients. Standard methods for enumerating Mycobacterium tuberculosis in patient sputum can miss large populations of viable M. tuberculosis cells that are unable to grow either on solid medium or in liquid medium unless the medium has been extensively diluted. Because these bacteria can be detected in liquid medium after limiting dilution, they have been termed differentially culturable or differentially detectable M. tuberculosis (DD- Mtb ). Treatment with isoniazid (H), rifampin (R), pyrazinamide (Z), and ethambutol (E) (HRZE) for 1 to 2 weeks has been shown to increase the representation of DD- Mtb in the sputum of drug-sensitive (DS) tuberculosis (TB) patients. However, little is known about DD- Mtb after longer periods of treatment with HRZE or in patients with drug-resistant (DR) TB who receive second-line therapies. Here, we measured the proportion of DD- Mtb cells in the sputum of 47 subjects, 29 with DS TB and 18 with DR TB, before initiation of treatment and at 2 weeks and 2 months thereafter. Prior to treatment, DD- Mtb cells represented the majority of M. tuberculosis cells in the sputum of 21% of subjects with DS TB, and this proportion rose to 65% after 2 weeks of treatment with first-line drugs. In subjects with DR TB, DD- Mtb cells were found in the sputum of 29% of subjects prior to treatment initiation, and this proportion remained steady at 31% after 2 weeks of treatment with second-line drugs. By 2 months, DD- Mtb cells were detected in the sputum of only 2/15 (13.3%) subjects with DS TB and in 0/15 of subjects with DR TB. One of the DS subjects whose sputum was positive for DD- Mtb at month 2 later experienced treatment failure.